Associations of VDR gene polymorphisms with risk of coal workers' pneumoconiosis in Chinese Han population. Issue 4 (17th June 2020) - Yang, Xi; Qin, Meiting; Cui, Shanshan; Zhang, Qi
Abstract: Some studies showed that the polymorphisms of vitamin D receptor ( VDR ) gene were associated with pulmonary diseases. However, the relationship between the VDR variations and susceptibility to coal worker's pneumoconiosis (CWP) remains unclear. The study aimed to determine the associations between VDR polymorphisms and susceptibility to CWP in Chinese Han population. The study involved 340 CWP patients and 312 healthy controls. The VDR polymorphisms were determined by DNA sequencing, and serum 25(OH)2D levels were detected by Ultra High-Performance Liquid Chromatography-Tandem Mass Spectrometry. The results showed that the VDR gene ApaI T allele increased the risk of CWP (OR = 1.486, 95% CI = 1.125–1.963, P = 0.006) and ApaI GT genotype as well as TT genotype increased the risk of CWP (GT vs. GG, OR = 1.461, 95% CI = 1.048–2.038, P = 0.025; TT vs. GG, OR = 2.673, 95% CI = 1.017–7.025, P = 0.039). Five haplotypes were identified and we found that the TGGT haplotype was associated with a lower risk of CWP (OR = 0.755, 95% CI = 0.603–0.946, P = 0.014). Meanwhile, multifactor dimensionality reduction analysis showed that the interaction between ApaI and exposure was the strongest, followed by TaqI and then BsmI . The study also found that the serum 25(OH)2D mean levels of the case group were significantly lower than that of the control group, and the serum 25(OH)2D mean levels of ApaI homozygous mutant and heterozygous mutant subjects were lower than that of the wild homozygosity, respectively ( P < 0.001). The results suggested that ApaI T allele and GT or TT genotype and lower 25(OH)2D levels were increased the risk of CWP in Chinese Han population.